Occupational characteristics of the surgeon’s work - MAIDANSCHI, Lidia (One Health & Risk Management, 2021)
Introduction. The healthcare profession is considered one of the most difficult and vulnerable intellectual specialties, which requires a specific professional responsibility. Medical activity is quite diverse and commonly differs from other jobs, depending on the type of occupational activity, working regimen and density. Surgeons are not excluded from this group due to the nature of work carried out on a daily basis. The surgeon's daily workload makes him/her susceptible to a variety of common work-related illnesses. They are exposed to a number of occupational hazards during their professional activity. These hazards include sharp wounds, blood-borne pathogens, latex allergy, laser pens, hazardous chemicals, anesthetic gases, equipment hazards, static posts, and stressors. However, many of surgeons pay little attention to their health and do not even seek appropriate help when needed. It has been observed that occupational risks pose a huge risk to the personal well-being of surgeons.Material and methods. A cross-sectional epidemiological research was carried out by using the descriptive method. The study involved surgeons from the Republic of Moldova. The research was conducted during 2020-2021 with the informed online consent from respondents. Participation in this study was absolutely voluntary. For this purpose, a comprehensive data collection tool has been developed. The questionnaire included 42 questions. The study involved 65 people with a mean age of 42.7 ± 1.9 years, the age ranged between 39-46 years. According to the gender criterion, women accounted for 35.4.8% and men - 64.6% of the respondents.Results. Within hospital settings, one of the most common occupational accidents is being injured by medical instruments or contacting biological agents. The respondents reported higher work-related risks in 47.7% of cases, 43.1% of respondents categorized these risks as medium harmful, and 9.2% of cases as being low at risk. 96.9% of respondents follow the sanitary-hygienic and anti-epidemic norms and requirements, whereas 3.1% of them do not comply with the rules. The respondents’ level of fatigue of at the end of the working day has a negative impact on their psycho-emotional state. The surgeons who participated in the study reported tiredness in 75.4% of cases, exhaustion in 16.9% of cases and only 7.7% of the respondents feel strong enough. As regarding the morbidity rate, 29.2% of surgeons stated to suffer from cardiovascular and digestive diseases, followed by 20% of diseases of the central nervous system, 16.9% - diseases of the endocrine system, 15.4% - diseases of the musculoskeletal system and eye disorders and 6.2% -diseases of the respiratory and urogenital system.Conclusions. Compliance with the working conditions and rules neither guarantees a decrease in stress levels at work nor provides protection against occupational diseases, as well as does not reduce the great amount of psychological and emotional stress due to the responsibilities of healthcare personnel regarding patient’s life and well-being.